Biopsychosocial Aspects of Atypical Odontalgia. (5th March 2013) - Ciaramella, A.; Paroli, M.; Lonia, L.; Bosco, M.; Poli, P.
Abstract : Background . A few studies have found somatosensory abnormalities in atypical odontalgia (AO) patients. The aim of the study is to explore the presence of specific abnormalities in facial pain patients that can be considered as psychophysical factors predisposing to AO. Materials and Methods . The AO subjects (n = 18 ) have been compared to pain-free (n = 14 ), trigeminal neuralgia (n = 16 ), migraine (n = 17 ), and temporomandibular disorder (n = 14 ). The neurometer current perception threshold (CPT) was used to investigate somatosensory perception. Structured clinical interviews based on the DSM-IV axis I and DSM III-R axis II criteria for psychiatric disorders and self-assessment questionnaires were used to evaluate psychopathology and aggressive behavior among subjects. Results . Subjects with AO showed a lower A β, A δ, and C trigeminal fiber pain perception threshold when compared to a pain-free control group. Resentment was determined to be inversely related to A β (rho: 0.62, P < 0.05 ), A δ (rho: 0.53, P < 0.05 ) and C fibers (rho: 0.54, P < 0.05 ), and depression was inversely related with C fiber (rho: 0.52, P < 0.05 ) perception threshold only in AO subjects. Conclusion . High levels of depression and resentment can be considered predictive psychophysical factors for the development of AO after dental extraction.